TRANSFORMASI DIGITAL DALAM PENGAWASAN PENGELOLAAN SAMPAH KOTA SERANG: PENERAPAN TEKNOLOGI UNTUK MENINGKATKAN EFISIENSI DAN TRANSPARANSI - Akbar Maulana, Muhammad; Syukri, Ahmad; Situmeang, Firman Yahya; Sulastri, Sulastri; Putri Pratama, Andayani; Nabil Al Fatih, Muhammad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Waste management problems in Serang City are still a serious challenge, especially in terms of efficiency and transparency of the monitoring system. The low utilization of technology in monitoring waste management causes delays in transportation, lack of data accuracy, and minimal community participation in the reporting system. This study aims to develop a digital transformation-based solution to improve the effectiveness of waste management supervision in Serang City. The method used in this activity is a participatory approach through socialization and training for village officials and the community regarding the use of digital technology, such as GIS-based applications, the Internet of Things (IoT), and real-time monitoring systems. This activity was implemented in Cipocok Jaya Village, involving academics, local government, and the community as the main partners. The results of the activity show that the use of digital technology can increase efficiency in monitoring waste transportation, minimize waste piles at vulnerable points, and strengthen transparency in the reporting system. Thus, digital innovation in waste management supervision can be an effective model in supporting sustainable environmental policies in Serang City.Keywords: Digital; Waste Monitoring; IoT Technology; Transparency.